Brincar em psicanálise : escutando professores de educação de crianças - Farias, Andrea Giulietti (2006)
Through the act of playing, the child tries to understand the world. It helps the child to understand himself as a subject, facilitates his motor development, his social relationships and his education. The object of the present study was to listen to the teachers about what they think and how they manage the child’s play. For that, we used psychoanalysis to understand the act of playing in a County School for children in Cuiaba, MS, Brazil, based on the spoken statement of the teachers. The main objective of this research was inquire what the teachers thought of playing and discuss with them some questions linked to the present subject. We used the psychoanalysis as the reference theory for this research. The psychoanalysis can help the educators to look at the children, the act of playing, and the education in a different way. The idea is to give more space for the new and not only to reproduce what is already known in the books and in the social establishment. In this process it is very important to listen to the teachers about their own practice, not only because the act of playing is indispensable for the formation of the subject but also because the teachers together with the children are responsible for the construction of knowledge, instruction and education. In the research development we used the qualitative approach, which can be considered a transformation in the way to think and to research in social sciences. The knowledge about the research subject is built during the research itself following an inductive process. The researcher is not worried about looking for evidences that would prove pre-established hypotheses. The conclusions are formed and consolidated through the data collection and analysis.In the present study, a group of teachers and school workers was formed to discuss the act of playing by the children. Six teachers and one school cook together with the researcher formed the eight people group. A total of seven weekly meetings happened in the school, every Wednesday from 4PM to 6PM between June and September of 2004. The meetings were taped with the permission of all participants. Seven tapes were produced, which were transcribed and analysed later. Based in the material taped in the weekly meetings, three categories were defined from meaningful and common elements derived from the teachers’ speeches. First, the conception of a new project; second, the aggressive play and its limits and; third, the act of playing and the reality. The first category resumes the teachers’ concerns in developing a proposition to use the act of playing to learn, their difficulties in developing and following such propositions and finally their assumptions that the act of playing is too distant from the school educational environment. The second category is based mainly in the aggression and violence in the act of playing and the school context. Additionally it approaches the teacher’s authority and the difficulty to impose limits in the act of playing. The third and last category implies how teachers are able to teach reality to children and if it would be possible to do so without the act of playing. In this last category, the material that was collected from 31 pedagogy’s second year students from UFMT was also included. From the results, comes the concept that the teachers view the act of playing as entertainment only. The creation of meetings in which teachers could discuss their views among themselves would be very interesting. In these meetings they would be able to talk, to be listened to and create new means and possibilities for their practice and education. In that way it would be easier for them to have a better idea of the reality and their limits. In these meetings they would also be able to discuss the act of playing as a form of learning inside the school and as part of their professional formation.